Oxford Reading Tress The Rainbow Machine for Grade1 - Roderick Hunt; Roderick Hunt (Karachi Oxford University Press, 2025)
This book is part of the phenomenally successful Oxford Reading Tree which is used to teach reading in 80% of primary schools. The stories within it are about much-loved Biff, Chip and...